The input reduction principle of agroecology is wrong when it comes to mineral fertilizer use in sub-Saharan Africa - (:unkn) unknown (My University, 2023)
Source Agritrop Cirad (https://agritrop.cirad.fr/606302/) * Autres projets (id;sigle;titre): ;DeSIRA;(EU) Development Smart Innovation through Research in Agriculture// ;CANALLS;(EU) Driving agroecological transitions in the humid tropics of Central and Eastern Africa through transdisciplinary agroecology Living Labs// ;RAIZ;(EU) Promoting agroecological intensification for resilience building in Zimbabwe//
Keywords: African Research